Dehydrated paunch and vegetable by-products for growing beef cattle - Nutsch, T.A.; Hunter, R.D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred beef heifers (avg wt 653 lb) were used in a feeding experiment to determine the relative feed value of dried paunch content, two separate vegetable processing by-products, and combinations of by-products with dryrolled corn. Consumption of the vegetable byproduct diets, both of which contained a high percentage of fat, was less than expected. Performance of cattle fed the by-product diets was less than that of cattle fed high-energy diets comprised of corn. However, when combined with corn, the vegetable by-product yielded performance similar to that of corn alone.
Keywords: Beef; Paunch; Vegetable by-product; Growing cattle